Elastic design of tapered beam-columns subjected to concentrated axial and transversal loads - Baptista, A. M. (2010)
Tapered members are an efficient solution for steel beams, allowing an adjustment of the cross-sections resistance to the applied loads. However, while the critical cross-section of uniform beams is always the one subjected to the most unfavourable load combination, it is not the case with tapered beams, since both acting and resistant values of the cross section internal loads vary along the beam length. So, one of the main problems in the design of these structural members lies on the determination of the beam critical cross-section where yielding occurs for the first time. This paper presents a method of calculation of analytical expressions for the elastic design of tapered beams subjected to bending and axial force. These relationships allow the beam critical section, its internal forces and the maximum loads carried by the beam at its elastic limit state, to be determined. Some examples are presented to show the possibilities of this proposal.